Odontomachus davidsoni sp. Nov. (hymenoptera, formicidae), a new conspicuous trap-jaw ant from Ecuador - Hoenle, Phillipp (2020)
One of the largest species in its genus, Odontomachus davidsoni Hoenle, Lattke & Donoso, sp. nov. is described from workers and queens collected at lowland forests in the Chocó-Darién bioregion in coastal Ecuador. The workers are characterized by their uniform red coloration, their large size (16–18 mm body length), and their frontal head striation that reaches the occipital margin. DNA barcodes (COI) and high resolution 2D images of the type material are provided, as well as an updated key for the Neotropical species of Odontomachus. In addition, a three-dimensional digital model of the worker holotype and a paratype queen scanned with DISC3D based on photogrammetry is presented, for the first time in a species description. Findings of large and conspicuous new species are uncommon around the world and suggest that these Ecuadorian rainforests may conceal many more natural treasures that deserve conservation. © Philipp O. Hoenle et al.